Agenda for social justice : solutions for 2020 - Muschert, Glenn W.; Budd, Kristen M.; Christian, Michelle; Perrucci, Robert (SSSP agendas for social justice, 2020)
The Agenda for Social Justice: Solutions for 2020 provides accessible insights into some of the most pressing social problems in the United States and proposes public policy responses to those problems. Written by a highly respected team of authors brought together by the Society for the Study of Social Problems (SSSP), it offers recommendations for action by elected officials, policy makers, and the public around key issues for social justice, including a discussion of the role of key issues of sustainability and technology in the development and timbre of future social problems. It will be of interest to scholars, practitioners, advocates, and students interested in public sociology and the study of social problems.